Combined interdisciplinary treatment of metastatic bone lesions – embolization, biopsy, ablation, and surgery in one operative sitting. (1st June 2022) - Haefeli, P C; Fuchs, B; Schelling, G; Baumgärtner, R; Möhl, P; Lopez Benitez, R; Link, B-C
Abstract: Objective: As a result of modern cancer treatment and thereby improved survival, many cancers spread to bone. Bone metastases may cause immobilizing pain and increase the risk of fracture even by inadequate or no trauma. Treatment of these patients should promptly address confirmation of the tumor entity, local control as well as adequate and lasting surgical stabilisation of the affected bone or joint. We present a setup to perform all the above in a single operative sitting. Methods: Required imaging is completed before initial consultation. The treatment plan is discussed in an interdisciplinary team according to the primary tumor and thereof resulting survival estimation, the imaging evaluation and patient's expectations and needs. In a single operative setup, the patients are treated by an interventional radiologist and an orthopaedic surgeon in a hybrid operating room. Thus, in one single setup the patient may undergo arteriogram to diagnose hypervascularity of the tumor followed by embolization if needed, CT-guided biopsy, percutaneous radiofrequency or cryotherapy ablation of the metastases for local tumor control and eventually surgical treatment with resection of the tumor, joint replacement or minimally-invasive stabilization as needed. Biopsy results may be discussed at inhouse tumor boards and adjuvant radio- or chemotherapy may be planned for the postoperative course. Results: Five combined procedures were performed in 5 patients (3 female, 2 male patients; median age 65 years (range 61–77)) each in one single operative sitting since October 2021. Three patients suffered from metastases of renal cell carcinoma, one each from thyroid carcinoma and breast cancer respectively. Metastases were located in the femoral meta- and diaphysis in 3 cases and in the acetabulum in 2 cases. Median duration of this multidisciplinary intervention was 375 min (251–426). Median length of hospital stay was 5 days (3–10). Median time from referral to definitive treatment was 24 days (17–32). All patients were able to walk with crutches immediately after treatment. No complications occurred. Conclusion: Combined multidisciplinary treatment of patients with metastatic bone disease is possible and may be favourable in respect of minimising the number of consultations, anaesthesias and interventions. This should lead to accelerated and pain-free mobilisation, thus maximising the patients' quality of life.